Indian philosophy of education - Humayun Kabir (Bombay : Asia Publishing, 1961)
The University of South Dakota offered an unusual new class entitled "Indian Philosophy of Education," during the 1972-73 school year. The class was initiated in response to Indian leaders' requests to the university for educational leadership, trained at the highest level possible (doctoral), in order to bring about Indian self-determination in education. Indian doctoral students participating in the class did all of their own teaching and furnished all input for the class. The first step in the class organization was the development of a set of basic beliefs common to all participants. These basic beliefs are examined in depth in 10 personal philosophies written by the participants. The Indian Philosophy of Education class expressed basic beliefs in "the need to be Indian...the need to define Indian-ness...that education is a moral development, not only an intellectual one...that contemplation is the way to reality and ultimate truth...that man without the Supreme Being is helpless and insignificant...that a successful person is one who has humility, self-denial, and wisdom...the need to know Indian ancestry...the return to Indian values." The 1972-73 class is the first faltering step toward a full-blown Indian education philosophy. Other Indian students will come along, build on, modify or add to these first building blocks--landmarks in Indian educational literature. (AH)
Microfiche.
Keywords: Educational philosophy